Memahami Teori Belajar Perilaku (Behaviorisme dan Teori Belajar Sosial Bandura serta Contoh Penerapannya) - Habsy, Bakhrudin All; Andani, Novia Fitri; Anggreani, Kintan; Buana, Imanda Riska Tri (Asian Journal of Early Childhood and Elementary Education, 2023)
This research aims to reveal Albert Bandura's behaviorist theory and its application in Arabic language learning. An in-depth study is needed to dissect Bandura's behaviorist theory, which is a new figure in the development of learning theories that have long been adhered to by these teachers. This research is library research, relying on bibliographic sources in the form of books and scientific journals related to research results, using descriptive analysis methods to read data and analyze Bandura's theoretical thinking. The application of behavioristic theory to stimulate student response stimuli is therefore important to understand that every human being has different characteristics and learning styles. The results of this research show that observational learning (modeling), which is better known as social learning theory and personality psychology, as well as programs based on the stimulus-response concept put forward by Bandura, have appeal in learning Arabic. Implementations that can be used include: presenting a lot of material with ḥiwār, imitating idioms, habituation, by not teaching qawā'id separately. Then, all learning objectives can be achieved by optimizing the language environment.